(untitled) (Texas Journal of Multidisciplinary Studies, 2022)
The article talks about a comparative assessment of the characteristics of physical development of athletic girls who specialize in gymnastics and aerobics. Our study was conducted among athletes 3-5 years old and a girl 14-20 years old. the conclusions drawn from the article can be used to train gymnastic girls.